(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the dietary profile of metabolic syndrome patients from the perspective of advanced glycation products, and to correlate it with lipid profile parameters. Methodology: A cross-sectional, retrospective study, carried out with data from medical records of patients with MS treated at the Nucleus for Research and Extension in Nutritional Genomics and Metabolic Dysfunctions – GENUT, Bahia State University (UNEB), Brazil – and by spontaneous demand. The amount of advanced glycation products was quantified from the 24h dietary recall. The data obtained were analyzed by the software R 4.0.4. Results: There was a predominance of females (84.1%) and family income of up to two minimum wages (40.8%). The average consumption of AGEs in the study participants’ diet was 7767 KU, higher than the recommended 7500 KU. Comparing the high and low consumption groups, a statistically significant difference was found (p<0.001). The analysis of metabolic syndrome factors with the consumption of AGEs showed a statistically significant positive association (p<0.005) between the HDL value in men and high consumption of AGE. Conclusion: Patients with metabolic syndrome treated at a nutrition clinic showed a high consumption of foods rich in advanced glycation products, which can constitute a risk to the health of these individuals. Studies that can determine acceptable values of AGEs carried out in larger populations and analysis of the amount of AGEs that include Brazilian regional foods will be fundamental for carrying out further research, making this knowledge more accessible.